2019
DOI: 10.15171/hpp.2019.07
|View full text |Cite
|
Sign up to set email alerts
|

The impact of indoor air temperature on the executive functions of human brain and the physiological responses of body

Abstract: Background: This study aimed to investigate the effect size (ES) of air temperature on the executive functions of human brain and body physiological responses.Methods: In this empirical study, the participants included 35 male students who were exposed to 4 air temperature conditions of 18°C, 22°C, 26°C and 30°C in 4 separate sessions in an air conditioning chamber. The participants were simultaneously asked to take part in the N-back test. The accuracy, electrocardiogram (ECG) signals and the respiration rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…In the present study, a similar magnitude of change in workload between the two air temperatures was observed as in the study of Lan et al 2 although the decrease in performance was smaller. Abbasi et al 3 observed that a 1°C increase in temperature above the comfortable temperature of 22°C caused about a 1.4% change in the workload. Maula et al 42 showed that slightly warm temperatures caused concentration difficulties and decreased the performance of a working memory task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, a similar magnitude of change in workload between the two air temperatures was observed as in the study of Lan et al 2 although the decrease in performance was smaller. Abbasi et al 3 observed that a 1°C increase in temperature above the comfortable temperature of 22°C caused about a 1.4% change in the workload. Maula et al 42 showed that slightly warm temperatures caused concentration difficulties and decreased the performance of a working memory task.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated temperatures that caused thermal discomfort have been shown to produce measurable changes in physiological responses including higher sympathetic nervous system activity as indicated by the increased ratio of low‐frequency power to high‐frequency power (LF/HF) of measured heart rate variability (HRV) 1‐3 . It is also well documented that increased temperatures and thermal discomfort can result in acute subclinical health symptoms such as headache, fatigue, and difficulty in concentrating 1,4,5 and that they can negatively affect the cognitive performance of both adults performing office‐like type of work and children performing schoolwork 3,6‐12 . Heat stress has additionally been shown to cause a significant decline in the performance of attention‐demanding tasks 13 …”
Section: Introductionmentioning
confidence: 99%
“…A 2019 study aimed to investigate the effect of air temperature on the executive functions of the human brain and body physiology responses. 20 The study found that unfavorable air temperatures may have a considerable effect on physiological responses and the cognitive functions among those working indoors. The moderate (70 °F [21 °C]) and low (66 °F [19 °C]) air temperatures had a very profound effect on changes in heartbeat rate, the accuracy of brain executive functions, and the response time to stimuli.…”
Section: Discussionmentioning
confidence: 94%
“…Understanding the chemical nature of signals and their receptors could help to design specific agonists or antagonists with the therapeutic role (Figure 1). Although humans are capable of maintaining their normal body temperature, the environmental temperature is known to affect several physiological functions such as feeding, digestion, and brain function in humans as well (Abbasi et al., 2019; Osilla et al., 2020). The identification of optimum temperature at which the body and brain function can be maximized with age could help to manage many age‐associated dysfunctions.…”
Section: Discussionmentioning
confidence: 99%